1985
DOI: 10.1056/nejm198506273122605
|View full text |Cite
|
Sign up to set email alerts
|

The Extent of Long-Term Moderate Drinking among Alcoholics Discharged from Medical and Psychiatric Treatment Facilities

Abstract: To assess the frequency of an evolution to stable moderate drinking among alcoholics coming to medical or psychiatric treatment facilities, we examined the five- to seven-year outcome for 1289 diagnosed alcoholics treated in our facilities during a two-year period (between 1973 and 1975). We obtained data from personal interviews, records, or both for 83 per cent of the sample. Only 1.6 per cent of the subjects met our definition of stable moderate drinking at follow-up, 15 per cent had become totally abstinen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
44
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(55 citation statements)
references
References 6 publications
10
44
1
Order By: Relevance
“…In fact, it has been suggested that behavioral treatment that includes moderation goals may be very appropriate given the cultural context of some ethnic groups (Bach & Bornstein, 1981). Similarly, when compared to men, women have shown a greater ability to drink moderately after behavioral treatment (Helzer et al, 1985;Miller & Joyce, 1979;Sanchez-Craig, Leigh, Spivak, & Lei, 1989), suggesting that women may be excellent candidates for behavioral interventions.…”
Section: Recommendations For Future Research On Treatment For Alcoholmentioning
confidence: 99%
“…In fact, it has been suggested that behavioral treatment that includes moderation goals may be very appropriate given the cultural context of some ethnic groups (Bach & Bornstein, 1981). Similarly, when compared to men, women have shown a greater ability to drink moderately after behavioral treatment (Helzer et al, 1985;Miller & Joyce, 1979;Sanchez-Craig, Leigh, Spivak, & Lei, 1989), suggesting that women may be excellent candidates for behavioral interventions.…”
Section: Recommendations For Future Research On Treatment For Alcoholmentioning
confidence: 99%
“…Follow-up research suggests that 90% of clients will relapse (Helzer et al, 1985). It is therefore likely that most persons in treatment will experience the relapse stage.…”
Section: Figure 1 Six Stages Of Change That Signal the Person's Readimentioning
confidence: 99%
“…While they announced that their results discounted the value of controlled-drinking therapy, they evaluated hospital treatment that certainly did not practice controlled-drinking therapy. And, of the four hospital treatment settings studied (Helzer et al 1985(Helzer et al : 1670 , "the alcohol -unit inpatients .. . fare[d] the worst.…”
Section: Evaluating Treatment Outcomesmentioning
confidence: 99%